Feasibility Study for Gas Power Plant Project in Kabupaten Muara Enim (The Indonesian Journal of Business Administration, 2013)
Kabupaten Enim Muara is one of the districts producing oil and natural gas in Indonesia, but in recent years a decline in lifting in the area which resulted in reduced revenue sharing from oil and gas sector gained Enim Muara District. In the calculation of revenue sharing, there was a significant decline in 2010 that only about 50% from 2009, while the sharing of natural gas, District of Muara Enim get an increase, and dipresiksi will continue to increase. Because of this, Kabupaten Enim Muara plans to increase revenue by utilizing the distribution of natural gas lifting results. One of the businesses that will be entered by the Kabupaten Muara Enim is the construction of gas power plants. Before running the gas power plant project, Kabupaten Enim Muara will conduct an analysis of the distribution of natural gas they will get, after which it will be converted into the amount of generating capacity that can be built. After that, it can be seen the amount of generating capacity that can be built, then the authors can calculate the amount of the costs incurred, and the price of electricity to be sold to PLN, because electricity prices are calculated based on the costs incurred by an electric generator. From the data that has been calculated, the authors could analyze the feasibility of a gas power plant for Development of these. From the feasibility study analysis conducted, it can be concluded that the construction of gas power plants is feasible to run, it can be seen from a positive NPV (USD 15,175,775), the IRR exceeds the cost of capital (13.12%), more than one PI (1.23), and also the project payback is relatively fast through 6.25 years. Keywords: lifing, profit sharing, gas power plants, feasibility studies, montecarlo.